DOI: 10.18130/v3kz3c
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Program Repair Using Genetic Programming

Abstract: Software quality is an urgent problem. There are so many bugs in industrial program source code that mature software projects are known to ship with both known and unknown bugs [1], and the number of outstanding defects typically exceeds the resources available to address them [2]. This has become a pressing economic problem whose costs in the United States can be measured in the billions of dollars annually [3].A dominant reason that software defects are so expensive is that fixing them remains a manual proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 212 publications
0
15
0
Order By: Relevance
“…There exist two general classes of techniques to improve the correctness, quality, robustness, and reliability of the software [7]: (1) The techniques that are applied during the software development process; these techniques can only be used for the development of the new systems; (2) the techniques that are applied to the software itself (e.g., testing, debugging, and verification).…”
Section: Background and Related Workmentioning
confidence: 99%
See 4 more Smart Citations
“…There exist two general classes of techniques to improve the correctness, quality, robustness, and reliability of the software [7]: (1) The techniques that are applied during the software development process; these techniques can only be used for the development of the new systems; (2) the techniques that are applied to the software itself (e.g., testing, debugging, and verification).…”
Section: Background and Related Workmentioning
confidence: 99%
“…As an example, Microsoft reported that Windows 2000 was released with more than 63,000 known bugs, largely due to insufficient resources [6]. On the other hand, post-deployment finding and repairing of bugs are considerably costly compared to the before-release ones [7]. Moreover, it might result in compromising the private or sensitive user information.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations